2012
DOI: 10.1039/c2jm30652b
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nanostructured W–Y2O3 materials by chemical methods

Abstract: A novel method for the fabrication of highly uniform oxide dispersion-strengthened (ODS) materials made by chemical processing is presented. The powders are fabricated by a two-step route starting with a chemical synthesis at room temperature, producing nanocrystalline yttrium doped tungsten trioxide hydrate precursor powders. Thermogravimetric analysis with evolved gas analysis revealed the presence of ammonium nitrate in the precursors. The second step is the reduction of the precursor in a hydrogen atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…There are many reports on the preparation of W-TiC nanoparticles by mechanical alloying (MA) [13]. However, nanoparticles used to agglomerate to some extent because of the high surface energies introduced by MA [14]. Besides, the milling process itself also produce detrimental phase by the wear of the milling equipment and media [13].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There are many reports on the preparation of W-TiC nanoparticles by mechanical alloying (MA) [13]. However, nanoparticles used to agglomerate to some extent because of the high surface energies introduced by MA [14]. Besides, the milling process itself also produce detrimental phase by the wear of the milling equipment and media [13].…”
Section: Introductionmentioning
confidence: 98%
“…And during the sintering process, TiC cores are expected to precipitate partially at the grain boundaries by precipitation from the supersaturated W matrix [10], resulting in homogeneous distribution of TiC nanoparticles in the matrix and grain boundaries. To prepare this core-shell structure, wet chemical method has shown high potential for industrialized manufacturing to produce molecular engineered nanomaterials with precise composition at very high purity, homogeneity, and controllable shape [14]. It is an efficient and low-cost method.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wahlberg et al reported a synthesis method which could control particle growth to produce uniformly yttrium doped nano-sized tungsten powders [10]. Zhou et al have developed ultrafine grained tungsten using resistance sintering under ultra-high pressure (RSUHP) [12].…”
Section: Introductionmentioning
confidence: 99%
“…The first is top-down via severe plastic deformation (SPD) to reduce the grain size of a monolithic component, such as equal-channel angular processing (ECAP), high pressure Additions of grain growth inhibitors are advantageous, as well as high pressure-assisted sintering with short thermal exposure, both of which could assist in simultaneously obtaining high density and fine grain size [8][9][10][11][12]. For example, Wahlberg et al reported a synthesis method which could control particle growth to produce uniformly yttrium doped nano-sized tungsten powders [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the milling process results in a detrimental phase because of the wearing of the milling equipment and the media. A wet chemical process can effectively fabricate and prepare complex nanomaterials while maintaining a precise composition with high purity and homogeneity [10,11,12]. A major challenge in the sintering of nanopowders is the achievement of full densification while preserving the nanoscale.…”
Section: Introductionmentioning
confidence: 99%